Analisa Kehilangan Crude Palm Oil (CPO) Dan Inti Kernel Dengan Metode Statistical Process Control (SPC) Untuk Meningkatkan Rendemen Di Pabrik Kelapa Sawit PTPN IV Adolina - Simamora, Rich Arif Adika; Siregar, Ninny; Banjarnahor, Marali (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2022)
As well as at PT. Perkebunan Nusantara IV unit Adolina, it is a company engaged in palm oil processing become semi-finished raw materials, i.e. CPO (Crude Palm Oil) and Kernel core. Similarly on losses on CPO and Kernel core occurred when production process, palm oil factory PTPN IV unit Adolina is very minimize loss as little as possible on CPO and Kernel core occurred. So, the purposes of the study are to find out how big losses on CPO and Kernel core, to increase OER and KER by using Statistical Process Control (SPC) method. Based on the analysis results obtained that, the amount of losses in station of Empty Bunches (X1 = 0.57%), Press (X2 = 0.56%), Nut (X3 = 0.10), Last Sludge (X4 = 0.39), Fibre Cyclone (X5 = 0.26), LTDS (X6 = 0.12), and Claybath (X7 = 0.01). Thus, there are four factors affect the occurrence of losses on CPO and Kernel core, i.e. Human Resources, Machine, and Raw Materials